Glucose measurement using portable blood glucose meters in dogs and cats - ATHANASIOU (Λ.Β. ΑΘΑΝΑΣΙΟΥ) L. V.; TSOKANA (ΤΣΟΚΑΝΑ Κ.Ν.) C. N.; SARIDOMICHELAKIS (Μ. ΣΑΡΙΔΟΜΙΧΕΛΑΚΗΣ) M. N. (Journal of the Hellenic Veterinary Medical Society, 2017)
Portable blood glucose meters (PBGMs) are small electronic devices that measure the concentration of glucose in whole blood. Due to the technological advances, measurement of glucose concentration is carried out in a small blood volume, and it is a relatively simple, quick and inexpensive procedure. PBGMs are frequently used in companion animal medicine, especially for the diagnosis and treatment monitoring of dogs and cats with diabetes mellitus and hypoglycaemia. The main factors affecting the precision of the measurement include: a) the device (manufacturer), the consumables (reagent strips) and their storage conditions; b) environmental conditions (temperature and possibly altitude); c) blood collection technique (site of sampling, cleanliness at the site of sampling, use of anticoagulants); d) patient factors (haematocrit, blood triglycerides, creatinine, uric acid and protein concentrations, drug administration); and, e) operator errors. Due to all these factors, readings of glucose concentration by PBGMs may differ from those of chemistry analysers, and this should be taken into account when shifting from one method to the other. Furthermore, because the results depend on the PBGM, the same device should be used and all measurements should be made under the same environmental conditions and using the same blood sampling technique for serial measurements of blood glucose to be comparable. Finally, all the above mentioned limitations of glucose measurement by PBGMs should be taken into consideration and the results should be interpreted along with the clinical signs and any other laboratory findings for optimal diagnostic and therapeutic decisions.